2013
DOI: 10.1007/s10877-013-9442-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical refinement of the automatic lung parameter estimator (ALPE)

Abstract: The automatic lung parameter estimator (ALPE) method was developed in 2002 for bedside estimation of pulmonary gas exchange using step changes in inspired oxygen fraction (FIO₂). Since then a number of studies have been conducted indicating the potential for clinical application and necessitating systems evolution to match clinical application. This paper describes and evaluates the evolution of the ALPE method from a research implementation (ALPE1) to two commercial implementations (ALPE2 and ALPE3). A need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Figure 1 summarizes the study protocol, indicating which measurements were performed in the intensive care unit and CT lab. Shunt and V/Q mismatch were measured using the automatic lung parameter estimator (ALPE) method [20,21] (ALPE integrated, Mermaid Care A/S, Nørresundby, Denmark). Lung aeration was assessed by CT scan analysis.…”
Section: Study Protocolmentioning
confidence: 99%
“…Figure 1 summarizes the study protocol, indicating which measurements were performed in the intensive care unit and CT lab. Shunt and V/Q mismatch were measured using the automatic lung parameter estimator (ALPE) method [20,21] (ALPE integrated, Mermaid Care A/S, Nørresundby, Denmark). Lung aeration was assessed by CT scan analysis.…”
Section: Study Protocolmentioning
confidence: 99%
“…In addition, recent attempts have been made to speed this process. Rule-based suggestions of FIO 2 control included in Beacon have shown that the process can be completed in 7.2 ± 2.4 min [51], and further reduction in time has been shown possible by fitting gas exchange parameters to data describing the dynamic response to FIO 2 change [50].…”
Section: Discussionmentioning
confidence: 99%
“…(ALPE) [4]. This same group also recently assessed new methods to reduce the time required to measure V A /Q distributions by this approach [5].…”
Section: Gas Exchange Methods For Ventilation/perfusion Distributionsmentioning
confidence: 99%